2002
DOI: 10.1034/j.1600-0897.2002.01078.x
|View full text |Cite
|
Sign up to set email alerts
|

High Altitude Residence During Pregnancy Alters Cytokine and Catecholamine Levels

Abstract: This study assessed the impact of high altitude residence during pregnancy on parameters of maternal immune and endocrine system function. Urinary catecholamines, and serum cytokines, estriol, and cortisol were assessed during pregnancy in women living at moderate or high altitude. Women residing at high altitude exhibited elevated levels of proinflammatory cytokines only during pregnancy, and tended to have higher levels of catecholamines during pregnancy than women living at lower altitude. These data sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 69 publications
3
17
1
Order By: Relevance
“…We also observed higher Placental growth factor (PlGF) levels at HA than LA by week 20 (Davila 2010, personal communication). Such findings are consistent with the hypothesized 2-stage model in which hypoxia is postulated to exert a stimulatory effect on angiogenic factors early in pregnancy,13 followed by reductions in the levels of such substances. These effects may influence the likelihood of reduced fetal growth 25…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We also observed higher Placental growth factor (PlGF) levels at HA than LA by week 20 (Davila 2010, personal communication). Such findings are consistent with the hypothesized 2-stage model in which hypoxia is postulated to exert a stimulatory effect on angiogenic factors early in pregnancy,13 followed by reductions in the levels of such substances. These effects may influence the likelihood of reduced fetal growth 25…”
Section: Discussionsupporting
confidence: 89%
“…Some reports describe higher IL-6 and TNF-α levels by mid-pregnancy,10 whereas others find that increases in IL-6 were complete after the first trimester and an absence of subsequent changes in IL-4, IL-10, or TNF-α 11. Chronic and acute hypoxia are also known to alter the levels of circulating cytokines both in the nonpregnant12 and in the pregnant condition,13 and to increase the frequency of the pregnancy complications of fetal growth restriction (FGR) and PE. Suggesting that alterations in cytokines might be involved in FGR associated with high-altitude (HA) residence, women living at 3100 versus 1600 m in Colorado had higher proinflammatory (IL-6, TNF-α) relative to anti-inflammatory (IL-10) cytokines during the second and third trimesters 13…”
Section: Introductionmentioning
confidence: 99%
“…Previously we found higher levels of the pro-inflammatory cytokines interleukin (IL)-6 and tumor necrosis factor relative to the anti-inflammatory IL-10 at 3100 than 1600 m in Colorado (Coussons-Read et al, 2002). To determine if differences in inflammatory response contributed to Andean protection from altitude-associated reductions in fetal growth, we compared pro- and anti-inflammatory cytokines in pregnant Andean and Bolivian women at low and high altitude (Davila et al, 2011).…”
Section: 0 Placental Factors Influencing Fetal Growthmentioning
confidence: 95%
“…The overall profile of cytokine production during pregnancy at high altitude is increased by sympatho-adrenal activation secondary to the interaction of hypoxia and pregnancy (11). It was reported that maternal circulating concentrations of the pro-inflammatory cytokines TNF-α, IL-6, and IL-8 were elevated late in normal pregnancy in women residing at high altitude compared to nonpregnant women (9). The interaction between the inflammatory cytokines and the vasoactive mediators has been investigated.…”
Section: Discussionmentioning
confidence: 99%